2021
DOI: 10.1177/20503121211016179
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of eHealth: A systematic review of the literature and observations in Denmark

Abstract: Objectives: The main objectives of this article are to systematically review the recent literature on patient safety in relation to the use of eHealth and to investigate how the Danish authorities supervise private eHealth clinics with regard to patient safety. Methods: Original studies reporting the association between patient safety and the use of eHealth as a means of communication between patients and healthcare providers were included. Four literature databases were searched for English-language articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies revealed that analyzing the status of regulations at the time of eHealth implementation is important for eHealth solution sustainability [ 21 , 36 , 42 ]. Maintaining patient safety and privacy policies would also significantly contribute to the sustainability of eHealth solutions [ 15 , 43 ]. In our study findings, a lack of policies and legislation was noticed in all the study areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that analyzing the status of regulations at the time of eHealth implementation is important for eHealth solution sustainability [ 21 , 36 , 42 ]. Maintaining patient safety and privacy policies would also significantly contribute to the sustainability of eHealth solutions [ 15 , 43 ]. In our study findings, a lack of policies and legislation was noticed in all the study areas.…”
Section: Discussionmentioning
confidence: 99%
“…In general, RCTs in eHealth are few despite occurrence of the COVID-19 pandemic situation, which has demonstrated a need for more evidence-based knowledge about the use of digital health technology in evaluating treatment effect, safety, and other aspects of patient management [34][35][36][37]. Patient education programs [38,39]; evaluation of psychological distress using teletechnology in diabetes [40]; use of mobile in suboptimal health [41], surgery care, and follow-up [42][43][44]; aphasia [44]; HIV consultations [38]; cancer symptom monitoring [45]; motor and cognitive function in stroke [46]; and COVID-19 follow-up [47] are areas where RCTs are used.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…In recent years, a significant increase in the use of eHealth has been observed, to which restrictions on in-person practice associated with the Coronavirus Disease 2019 (COVID-19) pandemic have also contributed [1]. According to the World Health Organization eHealth means "the cost-effective and secure use of information and communications technologies in support of health and health-related fields, including health-care services, health surveillance, health literature, and health education, knowledge and research" [2,3].…”
Section: Introductionmentioning
confidence: 99%